Ectopic ACTH-syndrome due to a Neuroendocrine Tumour of the Appendix - Perakakis, N.; Laubner, K.; Keck, T.; Steffl, D.; Lausch, M.; Meyer, P. T.; Burger, D.; Csanadi, A.; Seufert, J. (Experimental and Clinical Endocrinology & Diabetes, 2011)
Ectopic ACTH production causes 10% of Cushing’s syndromes. The diagnostic workup is difficult, can last more than 6 months (> 50% of cases), and the underlying tumour is still frequently not located (12%). Carcinoid tumours of the appendix are frequent and are revealed in 0.3% of patients undergoing routine appendectomy. However, neuroendocrine tumours of the appendix with ACTH production are an extremely rare entity.Here we report the case of a female patient with clinically overt Cushing’s syndrome due to ectopic ACTH-production from a carcinoid tumour of the appendix. During the diagnostic workup, repeated endocrine tests, multiple different imaging modalities and frequent and lengthy hospitalisations were necessary. Wrongly, even a neurosurgical pituitary exploration was performed. After 12 months from the initial admission, the tumour was finally detected by an 18F-fluoro-L-dihydroxyphenylalanine (18FDOPA PET) and an appendectomy followed by right hemicolectomy were performed. The patient recovered rapidly and the symptoms from the hypercortisolism were no more present.In this case, we discuss the multitude of problems, which may delay the diagnosis and the pitfalls, that should be avoided in order to locate the tumour and to initiate adequate therapy as early as possible. Furthermore, our case demonstrates the complexity of diagnostic procedures, which demand most of the times a multidisciplinary approach. In this setting, regular follow-ups in short time intervals and the use of novel imaging techniques can finally cut the diagnostic “Gordian knot”.
Keywords: glucocorticoids; pituitary adenoma; hyperandrogenemia